PTU-066 New Insight into the Mucosal Profile of Eicosanoid Mediators in Ulcerative Colitis. (4th June 2013) - Pearl, D S; Masoodi, M; Eiden, M; Shute, J K; Calder, P C; Trebble, T M
Abstract : Introduction: Ulcerative colitis (UC) is a relapsing remitting disorder of the colon with a recognised role for certain eicosanoid mediators derived from polyunsaturated lipid substrates. However, a detailed characterisation of the eicosanoids involved in UC is currently lacking. Using a comprehensive lipidomics approach, we profiled eicosanoids that could exhibit both pro- and anti-inflammatory function in inflamed and non-inflamed colonic mucosal biopsies from UC patients. Methods: Biopsies were taken from inflamed and nearby non-inflamed colonic mucosa (69 patients, 54 with paired inflamed and non-inflamed mucosa) from patients with symptomatic relapses. Inflammation was scored endoscopically and histologically. Mucosal lipid mediators were determined by LC-MS/MS lipidomics analysis. Univariate and multivariate statistical analyses were used to investigate the association of lipid mediators with the disease state as well as histologically assessed disease severity (using the Gomes scoring system). Results: Arachidonic acid (AA), but not eicosapentaenoic acid (EPA), derived eicosanoids (prostaglandin (PG)E2, PGD2, thromboxaneB2, 5-hydroxy-eicosatetraenoic acid (HETE), 11-HETE, 12-HETE and 15-HETE), were significantly (p < 0.001) higher in inflamed than non-inflamed mucosa and their concentrations correlated to histological severity. Conclusion: There is an upregulation of AA derived inflammatory mediators in UC. This research suggests new eicosanoid targets for research and therapeutic intervention. Disclosure of Interest: None Declared